A Contribuição do Fundo Constitucional do Norte para o desenvolvimento regional no período de 2012-2018 - CORRÊA, Alan Tiago (2022)
The creation of the Constitutional Fund for Financing of the North – FNO, administered by banco da Amazônia, has served as an essential tool for achieving the goal of minimizing the unequal distributions of credit historically more concentrated in the South and Southeast regions. In this direction, this work has as its basic objective to characterize the distribution of FNO credits, in the period from 2012 to 2018, in order to ascertain whether the FNO contributed significantly to the development of the Northern Region. Specifically, the problem raised in the study originated from the following question: Has the FNO really been an important credit line for the region's development process? The methodology was quantitative qualitative research, descriptive and through secondary data (database, reports and bibliographies specialized in the theme Regional Development and Regional Development Policies. The results show that the financing offered by the FNO positively impacts the economy of the resource-receiving States. The Fund's credits favor the increase in employment, income and production in the regions where the projects financed are carried out, as well as in other regions with which economic flows of partnerships are established.